On the electric field control of the MF radar scatterers in the lower E region over the magnetic equator - Gurubaran, S.; Dhanya, R.; Sathishkumar, S.; Paramasivan, B. (My University, 2007)
[1] Medium frequency (MF) spaced antenna radar observations from Tirunelveli (8.7°N, 77.8°E, geographic; 1.4°N magnetic dip) are used to examine the characteristics of lower E-region echoes and their possible association with the electrodynamical processes that drive the equatorial electrojet (EEJ). For the period (January 2006) under study, intense echoes were observed at 90 km and above at times of strong EEJ, indicating a possible electric field control of the radar scatterers. Under strong EEJ conditions, smaller pattern lifetimes, larger pattern scale sizes and axial ratios and strong pattern alignment along the geomagnetic field are routinely observed during this period. During the afternoon counter electrojet conditions, the electric field control of radar scatterers appears to weaken and the echo intensities are diminished. The work presented here calls for a detailed investigation that should address fundamental issues like the nature of the scatterers responsible for the MF radar echoes and their underlying generation mechanisms.
Keywords: Electric field; MF radar; Equatorial electrojet; Magnetic equator; Geomagnetic field; E-region